Media education and countering disinformation: A qualitative study of Egyptian youth - Tayie, Sally S. (Anàlisi, 2025)
Media education is essential for cultivating critical and analytical thinking, enabling individuals to evaluate and engage responsibly with media content. This study examines the role of media education in countering extremist ideologies and misinformation, focusing on how it fosters media awareness and literacy among university students. Using a qualitative approach, the research employed in-depth interviews with twelve purposively selected media professionals, educators and experts, alongside focus-group discussions with students from Cairo University, Misr International University and the American University in Cairo. Findings show strong expert consensus on the importance of equipping youth with media literacy skills. Students primarily engage with digital rather than traditional media but exhibit limited understanding of media education concepts. The study concludes by recommending strategies to strengthen media literacy initiatives and integrate media education within educational systems to enhance critical awareness and resilience against misinformation.